Trade-off between energy efficiency and collisions for MAC protocols of wireless sensor network - Jahan, Mohammad Saukat (2015)
Wireless sensor networks (WSNs) have the potential to connect the physical world with the virtual world by forming a network of sensor nodes (SN). In WSNs, efficient usage of resource is critical because sensor nodes are resource limited devices, also the network operations are often restricted the energy limitations. Hence, energy saving and reduce collision of sensor nodes are major design issue. Medium access control (MAC) protocols have a significant effect on the flexible, energy-efficient and collision free communication and performance of sensor networks. Therefore, it is necessary to develop a MAC protocol for trade-off between energy efficient and collision, which reduces delay, access collisions, resource consumption, and increases the system performance. This research investigates energy and collisions efficiency MAC protocols designed to extend the lifetime and manage the resource of WSNs. This research makes several significant contributions to the WSNs based on the IEEE 802.15.4 standards. First, the proposed incomplete cooperative game theoretic based MAC (GT-MAC) protocol, improves on the existing wireless sensor MAC protocols by offering significant network performance and lifetime extensions over the existing IEEE 802.15.4\Zigbee standards based WSN protocols. In this game, each sensor node estimates the current state of the game by detecting the channel and changes its equilibrium strategy by tuning to local contention parameters for trade-off between energy efficient and collision. Secondly, this research introduces a geographical and power based clustering algorithm (GPCA) for WSNs. Trade-off between energy efficiency and collisions in these approaches can be obtained by cluster formation, cluster-head election, data collecting at the cluster-head nodes to reduce data redundancy and thus, save energy. Finally, Cluster and Game Theory based MAC (CGT-MAC) algorithm manages the SNs resource efficiently by trade-off between energy efficiency and selecting a proper backoff period to eliminate the collisions among the SNs. In CGT-MAC, after geographically grouped into clusters, all SNs within a cluster based on current traffic conditions select a proper backoff period using the game theory for data transmission. Simulation models have been developed and simulated to verify the performance improvements of the proposed algorithms. Results indicate that the energy consumption is decreased to 25% in a moderately loaded (1pkt/sec) network to a heavily loaded (10pkt/sec) network over the standard of IEEE 802.15.4, EBA-15.4MAC, G-MAC, LEACH and ADAPT protocol. The throughput also improves by 34% in most scenarios of interest. This proves the viability of trade-off between energy efficiency and collisions for IEEE 802.15.4 based MAC protocols of WSNs.